Pengaruh Program Dakwah Al-Isyrafu Ad-Da’wi Yayasan Ar Risalah Al Khairiyah Terhadap Peningkatan Pengetahuan Agama Islam Peserta Rumah Quran Durratun Nasihah Kabupaten Serdang Bedagai - Suwardi Lubis; Supriyanto; Suhendri Hamzah (Program Studi Komunikasi dan Penyiaran Islam, 2022)
The purpose of this research was to find out the formulation of the problem in question, was: is there a significant effect on increasing the knowladge of the islamic raligion of the participants in the Durratun Nasihah House of Quran? This research was conducted because of the increasing knowledge of the islamic religion of the participants in the Durratun Nasihah House of Quran Serdang Bedagai Regency. This research uses the associative correlation menthod with a quantitative approach. The sampling technique was determined by totality sampling. The results of the analysis show that there is a positive and significant influance between the two veriables, it can be seen that the correlation coefficient value is at a significant level of 5%, was r = 0.695 > r table (0.000), which r count > r table it is concluded that the two have a relationship, and also the significance level is 0.000. The major contributions are: KD : r² x 100% = (0.695)² x 100% = 48.30%. From the above calculation results, it can be seen that the contribution of variable X to variable Y is 48.30% and 51.70% is determined by another.